Profil sistem integrasi usaha sapi perah dengan tanaman hortikultura di Nongkojajar Kecamatan Tutur Kabupaten Pasuruan - Richard E. M. F. Osak; Budi Hartono; Zainal Fanani; Hari Dwi Utami (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The study tended to evaluate dairy-horticulture integration system among dairy farmers as the member of the Koperasi Peternak Sapi Perah (KPSP) Setia Kawan in Nongkojajar, Pasuruan regency. The method of the study was survey and data were analyzed descriptively. The study found that the revenue earned from dairy cattle farming was IDR 23.357.321,17±9.938.351 (46,54%), horticultural crops farming was IDR 10.030.225,41±7.752.962 (19.99%), forage fodder was IDR 12.380.163,93 ±9.569.370 (24.67%) and plant waste feed was IDR 1.595.665,57±1.233.386 (3.18%) and the revenue derived from biogas and bioslurry in dairy-horticultural farming system was about IDR 1.087.099,07±300.209 (2.17%) and 1.737.147,54±1.075.414 (3.46%) respectively. The average biogas production per year was found about 285.39 ± 176.68 kg which was equal to LPG, but the farm household in the study area only used 100.80 ± 27.84 kg per year. Keywords: Profile, dairy, horticulture, integration, Nongkojajar